The Hounds of Sunset - Pargeter E. Edith (London, Headline, 1976)
The third chronicle traces the destiny of the warring brothers of Gwynedd. Powerful Prince Llewelyn still treasures his vision -Wales as one, united against the threat of the English kings. The dream seems near fulfilment, until Edward, vigorous, ambitious and arrogant, takes old Henrv's place on the English throne - and more than his share of power.Troubles loom nearer home, too, where the youngest ot the Welsh brothers - David, blue-eyed, charming and deadly - is plotting his downfall. Threatened on all sides, Llewelyn looks for comfort from the beautiful Eleanor de Montfort, the jewel in his crown and the only shining star as night falls on his dreams of power.